2021
DOI: 10.37093/ijsi.950553
|View full text |Cite
|
Sign up to set email alerts
|

Financial Performance Ranking of Turkish Participation Banks by Entropy and Mairca Method

Abstract: Participation banking, also referred to as Islamic banking, is also known as interest-free banking. The participation banking sector emerged in the 1980s. The participation banking sector is a complement to the Turkish banking sector. Therefore, measuring the performance analysis of this sector has become even more important. The difference from the traditional banking system is that it performs its banking transactions on the basis of the interest-free principle. The participation banking sector, which is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
2
0
0
2
Order By: Relevance
“…According to the GRA results based on entropy, between 2019-2021, Ziraat Participation and Vakıf Katılım showed the most successful performance, while Albaraka Türk showed the lowest performance. These results are compared with the literature, with the studies of Bektaş (2021) and Çelik (2020) for Ziraat Participation, and Gençtürk et al (2021), Odabaş and Bozdoğan (2020), Karavardar andÇilek (2020), andAyrçay et al (2017) is in line with the studies. Albaraka Türk's lowest performance was found in Yurttadur et al (2022), Bektaş (2021), Odabaş and Bozdoğan (2020), Karakaya (2020) and Gezen (2019) are in line with the studies.…”
Section: Tesamsupporting
confidence: 79%
See 3 more Smart Citations
“…According to the GRA results based on entropy, between 2019-2021, Ziraat Participation and Vakıf Katılım showed the most successful performance, while Albaraka Türk showed the lowest performance. These results are compared with the literature, with the studies of Bektaş (2021) and Çelik (2020) for Ziraat Participation, and Gençtürk et al (2021), Odabaş and Bozdoğan (2020), Karavardar andÇilek (2020), andAyrçay et al (2017) is in line with the studies. Albaraka Türk's lowest performance was found in Yurttadur et al (2022), Bektaş (2021), Odabaş and Bozdoğan (2020), Karakaya (2020) and Gezen (2019) are in line with the studies.…”
Section: Tesamsupporting
confidence: 79%
“…These results are compared with the literature, with the studies of Bektaş (2021) and Çelik (2020) for Ziraat Participation, and Gençtürk et al (2021), Odabaş and Bozdoğan (2020), Karavardar andÇilek (2020), andAyrçay et al (2017) is in line with the studies. Albaraka Türk's lowest performance was found in Yurttadur et al (2022), Bektaş (2021), Odabaş and Bozdoğan (2020), Karakaya (2020) and Gezen (2019) are in line with the studies. In addition to these, according to the results of the analysis, it can be concluded that state participation banks performed better than private participation banks between the years 2019-2021.…”
Section: Tesamsupporting
confidence: 79%
See 2 more Smart Citations